Residential childcare worker perceptions of work-related achievement and pride - Brend, Denise Michelle; Olaniyan, Oyeniyi Samuel; Collin-Vézina, Delphine (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction Multiple risk and protective factors influence the wellbeing and retention of child protective and youth justice professionals. Less attention has been given to empirically understand how residential childcare workers (RCW) experience these factors. A sense of pride and of achievement may be related to competence and satisfaction, which have been identified as protective factors against staff turnover. Methods Responses to the Secure Base Interview Protocol question “What aspects of caring for (name of child in their care) have given you the greatest sense of pride or achievement?” were extracted from individual interview transcripts from Canadian RCW and analyzed using the Interpretive Description methodology. Themes were aggregated using the thematic analysis technique to create descriptions of RCW pride and achievement. Results The RCW identified many experiences of work-related pride and achievement while caring for children and youth. These positive experiences were described to occur contingent on the level of mutuality and trust in the helping relationship shared between the RCW and child or youth in their care. Discussion The reciprocal nature of the relationships described by RCW that gave rise to their felt sense of pride and accomplishment is a novel finding. Future work is indicated to better understand how protective factors related to RCW wellbeing may indeed be relationally constructed and dependent.